Does Leader-member Exchange Matter on Doctor-patient Relationship in China? - Zeng, W.L.; Ma, S. (EURAM Annual Conference 2019, 2019)
This study investigated the relationships among leader–member exchange (LMX), Doctor-patient relationship (DPR), work engagement and turnover intention. Drawing on the job demands–resources model and conservation of resources theory, we expected DPR as challenge demand, mediates the relationship between LMX and work engagement, and the relationship between LMX and turnover intention. Two-wave data collected from 381 doctors in a public hospital in China supported our hypothesized model. Our results showed that LMX positively related with both DPR and work engagement, but negatively related with turnover intention. In addition, DPR partially mediates the path from LMX to work engagement, but also partially mediates the path from LMX to turnover intention. This study contributes to the limited studies on managing the escalating DPR issue in China from organizational perspective. In addition, this study also contribute to the development of JD-R model by investigating the validity of challenge demand concept with evidence from healthcare occupation in China. Theoretical and practical implications are discussed.